Analysis of Saccharomyces cerevisiae deletion mutants displaying a modified carbon flux under wine fermentative conditions - Madlanga, Ncedile Hamilton (Stellenbosch : University of Stellenbosch, 2009)
Thesis (MSc (Wine Biotechnology))--University of Stellenbosch, 2009.